Transformational Leadership on Organizational Citizenship Behavior: The Mediating Organizational Culture at PT Rosan Permai - Enjang, Satriyo; Fatoni, Fandi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The purpose of this research is to test and analyze the influence of transformational leadership (TL) on Organizational Citizenship Behavior (OCB) through organizational culture (OC). This research is causal research with a quantitative approach involving 44 employees of PT Rosan Permai. The sampling technique used saturation for 44 respondents. The statistical analysis used in this research is SEM PLS with the help of SmartPLS 3.0 software. The analysis results obtained from this research show that TL has no effect on OCB. TL has a significant positive effect on CO. Organizational culture has a significant positive effect on OCB. Organizational culture in this study was able to mediate the influence of TL and OCB. From this research it can be concluded that transformational leadership can improve and develop Organizational Citizenship Behavior through organizational culture at PT Rosan Permai.